2012
DOI: 10.3892/ol.2012.839
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and bevacizumab for recurrent malignant glioma

Abstract: Abstract. Over 65,000 primary brain tumors are diagnosed annually in the US alone. Malignant gliomas represent more than one-third of such cases. Despite advances in neuroimaging, surgical techniques, radiotherapy and chemotherapy, the survival rate of this disease remains poor. The introduction of agents which disrupt the function of vascular endothelial growth factor (VEGF) and its receptors to glioma therapy has resulted in an unusually high percentage of patients experiencing radiographic responses. Bevaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…It is unclear whether BVZ is unique among other antiangiogenic agents in its role in the treatment of recurrent malignant gliomas, as well as the optimum combination of BVZ and agents having other mechanisms of action. 37,4245,47,52 Finally, the combination of BVZ and radiosurgery may afford some benefits, as described later, though this remains an area of active investigation and controversy. 61 …”
Section: Chemotherapymentioning
confidence: 95%
“…It is unclear whether BVZ is unique among other antiangiogenic agents in its role in the treatment of recurrent malignant gliomas, as well as the optimum combination of BVZ and agents having other mechanisms of action. 37,4245,47,52 Finally, the combination of BVZ and radiosurgery may afford some benefits, as described later, though this remains an area of active investigation and controversy. 61 …”
Section: Chemotherapymentioning
confidence: 95%
“…27,28,32,[38][39][40][41][42][43][44][45][46][47] In addition, several retrospective studies have also been reported combining bevacizumab and irinotecan; carboplatin; carboplatin and cetuximab; carboplatin, etoposide, and ifosfamide; lomustine; carmustine; etoposide; or temozolomide. [48][49][50][51][52][53][54][55][56][57][58] Although these small studies are not easily compared due to their size and various patient populations, the consensus to date has been that no combination significantly surpasses the outcomes of bevacizumab monotherapy for recurrent glioma. 9 …”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%
“…By removing available circulating VEGF, frequently overexpressed in malignant cancer, bevacizumab inhibits the proliferation of endothelial cells and the formation of new blood vessels, frequently resulting in remarkable responses 14 15…”
Section: Introductionmentioning
confidence: 99%